Indonesia Rancang Bangun Sistem Pemantauan Distribusi Sembako Tanggap Bencana Berbasis Sensor Sidik Jari dan Komunikasi Nirkabel NRF24L01: - - Junindo Abdillah; Gipin Mosliano; Nandika Vadya Pratama (JURNAL TEKNOLOGI INDUSTRI, 2026)
The distribution of food aid during disaster situations often faces challenges related to monitoring and accurate recipient verification. This study aims to design and implement a food distribution monitoring system based on a fingerprint sensor and NRF24L01 wireless communication module. The system consists of a transmitter unit equipped with a fingerprint sensor for recipient verification and a receiver unit that displays data on an LCD and uploads it to Google Sheets via an internet connection. The research method involves hardware and software design followed by communication performance testing under Line of Sight (LOS) and Non-Line of Sight (NLOS) conditions. The evaluation parameters include transmission distance and data delivery success rate. The results show that the system can reliably transmit data up to 15 meters under LOS conditions and 10 meters under NLOS conditions, with significant performance degradation beyond these distances due to physical obstacles. The proposed system demonstrates potential as a low-cost and practical solution for wireless-based disaster aid distribution monitoring.